Correlates of Child Labour and Poverty Alleviation among Low-Income Earners in Kwara State, Nigeria - KADIRI, Bolarinwa Ismaila; Mustapha Olanrewaju Aliyu; OLOYEDE Babatunde Najeeb; Dunmade Olaniyi Emmanuel; OLOWOLENI Modupe Folaranmi (Universitas Kuningan, 2020)
The study explores the correlations between child labour and poverty alleviation among the low-income earners in Kwara State, Nigeria. Survey design and purposive sampling method were employed to select the respondents from the 3 Senatorial districts of Kwara state. The Chi-square (X2 ) method of dataanalyses then used to analyze the data obtained. The result is a 2x2 table is taken a degree of freedom of (r-1) (k-1) = 1 at 5% level of significance, X2t = 3.84 and X2c = 0.17. Since the X2t X2c, it shows that a relationship exists between child labour and poverty reduction in Kwara state. The study concluded that governments, at the federal and state levels, are yet to live up to their expectations. Their inability to provide jobs for graduates have discouraged most of the children to have an interest in schooling. Therefore, the government should provide a potent economic environment that will encourage those with genuine ideas to engage in promising economic activities. This will lift a lot of low-income earners to higher pedigree. Similarly, parent/guardians in the low-income groups should be encouraged that extra efforts in assisting their children not to engage in child labour but schooling as a future investment with a higher rate of return.